Medicinal Plant Images - Cock, I.E. (Pharmacognosy Communications)
Acanthosicyos horridus (commonly known as nara melon) is a member of the watermelon family that grows most prevalently in the coastal regions of the Namib desert, Namibia. It also occurs as far south as Northern Cape province in South Africa and as far north as southern Angola. The fruit can be eaten raw although it contains cucurbitacins (which irritate the mouth) and was traditionally eaten dried. The nuts inside the fruit have been a staple diet of the Topnaar people of the Namib Desert for millennia.[1, 2] Nara also has uses in traditional medicine. The fresh fruit is used to relieve stomach pains, oils from the seeds are used to protect from sunburn and as a moisturiser, and a decoction of the roots is used in the treatment of a wide variety of ailments including nausea, stomach disorders, STI’s, kidney disorders, arteriosclerosis, wounds and chest pains.[1] This photograph was taken in in the Namib Desert near Walvis Bay, Namibia in December 2012 by Dr Ian Cock.